2007
DOI: 10.1159/000099106
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Balloon Inflations Do Not Diminish ST Segment Elevation even though Coronary Collateral Recruitment Is Promoted in Pigs

Abstract: Objective: Attempts to demonstrate preconditioning during repeated angioplasty balloon inflations (BIs) have not been universally successful. The main obstacle is that the first BI is unreliable, due to the variable degrees of occlusion by the deflated balloon. In the present study, we examined whether ST segment elevation decreases and evaluated its relation to collateral recruitment during repeated angioplasty BIs in the pig. Methods and Results: Twenty male pigs, 7 months old, under general anesthesia, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…I: at 5 wk, myocardial perfusion is globally lower than at 1 wk. J: average sizes of 15 O-radiowater PET perfusion defects show that approximately half of the LV is affected in this model (by either infarction or reversible ischemia). K: 18 F-FDG PET shows 28 and 36% of partially and nonviable myocardium of the LV, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…I: at 5 wk, myocardial perfusion is globally lower than at 1 wk. J: average sizes of 15 O-radiowater PET perfusion defects show that approximately half of the LV is affected in this model (by either infarction or reversible ischemia). K: 18 F-FDG PET shows 28 and 36% of partially and nonviable myocardium of the LV, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…In the dog model of intermittent 2-min coronary occlusions (8 times per day over 20 days) by a percutaneous pneumatic occluder, it was shown that the rate of collateral development was slower in dogs with poorer endogenous collaterals (7). Furthermore, the three repeated brief coronary occlusions by a balloon inflation appeared to recruit some collaterals in a porcine model but did not diminish ST-segment elevation (15), demonstrating that the preexisting collateral anastomoses need to enlarge over a few days to prevent transmural myocardial infarction in pigs. In our model, the few newly formed collaterals seen at 1 wk via angiography in pigs with transmural infarction were regressed by 4 wk, probably because infarcted myocardium needs only little blood flow, which corroborates the findings of a recent clinical study (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations